Development of an ASV for Oceanographic Monitoring on the Huarmey Coast - Velasco M, L.; Balbuena, J.; Gonzales, J.; Cuellar, F. (Institute of Electrical and Electronics Engineers, 2021)
This paper presents the desing and preliminar simulations of an Autonomous Surface Vehicle (ASV) for monitoring oceanographic and meteorological parameters in the coastal areas of Huarmey-Peru, as well as the development of a control algorithm for its autonomous navigation. The development of the ASV aims to allow the monitoring and collection of sea water quality parameters (pH, turbity, salinty, conductivity, temperature, nitrate, chlorophyll and pythoplankton), current velocity and bathymetric measurement, which is relevant for environmental monitoring and provide information for sustainable fishering and aquiculture activities. A non-linear controller is implemented based on Differential Flatness method in order to track the desired path generated by the ASV.Simulations are presented to validate the control strategy with different desired path and generating disturbances, showing the response of the state and control variables of the system.
Keywords: Flatness (cosmology); Unmanned surface vehicle; Environmental science; Bathymetry; Computer science; Controller (irrigation); Remote sensing; Marine engineering; Engineering; Oceanography; Geology; https://purl.org/pe-repo/ocde/ford#2.02.05